Effect of Monodisperse Coal Particles on the Maximum Drop Spreading after Impact on a Solid Wall; Energies; Vol. 16, iss. 14 - Ashikhmin A. E. Alexander Evgenjevich; Khomutov N. A. Nikita Andreevich; Volkov R. S. Roman Sergeevich; Piskunov M. V. Maksim Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2023, 2023)
Title screen